Green Marketing: Challenges and Suggestions: Promoting Eco-friendly Products and Environmental Awareness (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Marketing means selling and purchasing of goods and services. But when these selling and purchasing are done to keep in mind the importance of environment then it is called Green Marketing. It means marketing of those products which are friendly to environment. It has be easily acceptable by consumers. Many standards are fixed for the verification of product that they are up to standard or not. Consumers are giving the preference to these products. It is a modern concept of marketing. It arises due to harmful effect on environment all over the world. Environmental issues are rising day by day, so it has become important for us to protect environment to save our future life. India is a developing country and also giving the priority to this sector. The purpose of this research paper is to find out what are the challenges and purpose of Green Marketing because mostly people are unaware in the field of Green Marketing. It is a typical situation for India. Because in India mostly people belong to rural area and they do not know about all these. So it has become the duty of government to spread awareness about Environmental Protection and to encourage the people to purchase those products which are Eco-friendly. The cost of the product at initial stage may be high but it would be cheap in coming future. No doubt Green Marketing is necessary for the clean environment to the coming generation.